Deficiency of Adenosine Deaminase 2 in Adults and Children: Experience From India. Issue 2 (26th December 2020) - Sharma, Aman; Naidu, GSRSNK; Sharma, Vikas; Jha, Saket; Dhooria, Aaadhar; Dhir, Varun; Bhatia, Prateek; Sharma, Vishal; Bhattad, Sagar; Chengappa, K. G.; Gupta, Vikas; Misra, Durga Prasanna; et al.
Abstract : Objective: Deficiency of adenosine deaminase 2 (DADA2) is a potentially fatal monogenic syndrome characterized by variable manifestations of systemic vasculitis, bone marrow failure, and immunodeficiency. Most cases are diagnosed by pediatric care providers, given the typical early age of disease onset. This study was undertaken to describe the clinical phenotypes and treatment response both in adults and in children with DADA2 in India. Methods: A retrospective analysis of pediatric and adult patients with DADA2 diagnosed at various rheumatology centers across India was conducted. Clinical characteristics, diagnostic findings, and treatment responses were analyzed in all subjects. Results: In total, 33 cases of DADA2 were confirmed in this cohort between April 2017 and March 2020. Unlike previous studies, nearly one‐half of the confirmed cases presented during adulthood. All symptomatic patients exhibited features of vasculitis, whereas constitutional symptoms and anemia were more common in pediatric patients. Cutaneous and neurologic involvement were common, and 18 subjects had experienced at least one stroke. In addition, the clinical spectrum of DADA2 was expanded by recognition of novel features in these patients, including pancreatic infarction, focal myocarditis, and diffuse alveolar hemorrhage. Treatment with tumor necrosis factor inhibitors (TNFi) was initiated in 25 patients. All of the identified disease manifestations showed marked improvement after initiation of TNFi, and disease remission was achieved in 19 patients. Two cases were complicated by tuberculosis infection, and 2 deaths were reported. Conclusion: This report presents the first case series of patients with DADA2 from India, diagnosed by adult and pediatric care providers. The findings raise awareness of this syndrome, particularly with regard to its presentation in adults.